13C magnetic resonance spectroscopy measurements with hyperpolarized [1‐13C] pyruvate can be used to detect the expression of transgenic pyruvate decarboxylase activity in vivo. Issue 2 (21st September 2015) - Dzien, Piotr; Tee, Sui‐Seng; Kettunen, Mikko I.; Lyons, Scott K.; Larkin, Timothy J.; Timm, Kerstin N.; Hu, De‐En; Wright, Alan; Rodrigues, Tiago B.; Serrao, Eva M.; Marco‐Rius, Irene; Mannion, Elizabeth; et al.
Abstract : Purpose: Dissolution dynamic nuclear polarization can increase the sensitivity of the 13 C magnetic resonance spectroscopy experiment by at least four orders of magnitude and offers a novel approach to the development of MRI gene reporters based on enzymes that metabolize 13 C‐labeled tracers. We describe here a gene reporter based on the enzyme pyruvate decarboxylase (EC 4.1.1.1), which catalyzes the decarboxylation of pyruvate to produce acetaldehyde and carbon dioxide. Methods: Pyruvate decarboxylase from Zymomonas mobilis ( zm PDC) and a mutant that lacked enzyme activity were expressed using an inducible promoter in human embryonic kidney (HEK293T) cells. Enzyme activity was measured in the cells and in xenografts derived from the cells using 13 C MRS measurements of the conversion of hyperpolarized [1‐ 13 C] pyruvate to H 13 CO 3 – . Results: Induction of zm PDC expression in the cells and in the xenografts derived from them resulted in an approximately two‐fold increase in the H 13 CO 3 – /[1‐ 13 C] pyruvate signal ratio following intravenous injection of hyperpolarized [1‐ 13 C] pyruvate. Conclusion: We have demonstrated the feasibility of using zm PDC as an in vivo reporter gene for use with hyperpolarized 13 C MRS. Magn Reson Med 76:391–401, 2016. © 2015 The Authors. Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.